2010
DOI: 10.1073/pnas.1009307107
|View full text |Cite
|
Sign up to set email alerts
|

Duration of estrogen deprivation, not chronological age, prevents estrogen's ability to enhance hippocampal synaptic physiology

Abstract: Whether estrogen replacement is beneficial to cognitive health is controversial. Some studies have shown that estrogen replacement therapy (ERT) relieves memory impairment associated with menopause in women, whereas others suggest that estrogen not only is incapable of providing a benefit, but actually can be detrimental. One possible explanation for this discrepancy in study findings could be the varying time after menopause at which ERT is initiated. It has been proposed that a critical period exists during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
78
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 57 publications
10
78
1
Order By: Relevance
“…As such, fundamental changes may occur in the brain during chronic treatment (e.g., downregulation of ERs) that do not occur after acute treatment. On the other end of the hormonal spectrum, long-term ovariectomy decreased hippocampal neurogenesis and prevented acute E 2 from increasing cell proliferation (Tanapat et al 2005), which is consistent with the detrimental effects of long-term ovariectomy on LTP and memory discussed above Smith et al 2010;Vedder et al 2014). Collectively, these data suggest that either chronically elevated E 2 levels or long-term hormone deprivation may permanently alter the hippocampus to reduce its responsiveness to E 2 .…”
Section: Neurogenesissupporting
confidence: 68%
See 2 more Smart Citations
“…As such, fundamental changes may occur in the brain during chronic treatment (e.g., downregulation of ERs) that do not occur after acute treatment. On the other end of the hormonal spectrum, long-term ovariectomy decreased hippocampal neurogenesis and prevented acute E 2 from increasing cell proliferation (Tanapat et al 2005), which is consistent with the detrimental effects of long-term ovariectomy on LTP and memory discussed above Smith et al 2010;Vedder et al 2014). Collectively, these data suggest that either chronically elevated E 2 levels or long-term hormone deprivation may permanently alter the hippocampus to reduce its responsiveness to E 2 .…”
Section: Neurogenesissupporting
confidence: 68%
“…In these studies, two injections of E 2 given 24 h apart were unable to increase LTP in rats ovariectomized for 19 mo prior to treatment (Smith et al 2010). Importantly, this loss was not due to aging, as rats of the same age ovariectomized just 1 mo prior to E 2 treatment exhibited increased LTP in response to E 2 (Smith et al 2010).…”
Section: Synaptic Plasticitymentioning
confidence: 85%
See 1 more Smart Citation
“…S3). It should be pointed out that degradation of ERα following LTED may explain not only the loss of E2 neuroprotective action observed in our study but the loss of other critical E2 actions reported previously following LTED, such as loss of E2 enhancement of long-term potentiation (LTP) and synaptic density (24) and elevation of choline acetyltransferase (25). Thus, our results may help to explain the loss of other well-known estrogen actions in the hippocampus following prolonged hypoestrogenicity.…”
Section: Discussionmentioning
confidence: 56%
“…These generally nonsignificant findings in younger and older postmenopausal women contrast with results of studies in rodents and nonhuman primates. Here, E2 affects cognitive performance, synaptic plasticity, and neurophysiological properties in a manner that can vary with age or the interval between ovariectomy and hormone replacement (10,(32)(33)(34)(35). Effects are tissue-specific and may reflect, in part, the increased degradation of estrogen receptor-α that occurs with aging or after ovariectomy (36,37).…”
Section: Discussionmentioning
confidence: 99%